Micropatterned κ-carrageenan-PVP-PEG hydrogels as a templet for head and neck cancer spheroid culture - Nadia Halib; Zainah Adam; Maznah Mahmud (MediPoeia, India, 2024)
J Appl Pharm Sci, 2021; 11(05):015–021.